The Effect of Servant Leadership on the Psychological Well-being of the Workers: A Study of the Mediating Effect of Trust in a Leader “Applied on the Egyptian Commercial Banking Sector” - El-Zohiry, Amira (The Arab Journal of Administration, 2021)
This research sought to determine the effect of servant leadership on the psychological well-being of the workers in the presence of trust in leader as a mediating variable, and was conducted on a sample of 350 workers in the commercial banking sector. The primary data was collected based on the researcher’s in-depth interviews with employees in the public sector banks (Banque Misr, National Bank of Egypt) and in the private sector (Faisal Islamic Bank, National Bank of Kuwait), and the survey lists distributed were divided into four parts. The first part to measure servant leadership, the second part to measure trust in leader, the third part to measure psychological well-being, and the fourth part to measure personal and functional variables. The research was designed based on four main hypotheses. It has been proven that there is a significant effect between the dimensions of trust in leader and the psychological well-being of the workers, between the dimensions of servant leadership and the psychological well-being of the workers, and a mediating effect between the servant leadership and the psychological well-being of the workers. The research made several recommendations to enhance servant leadership, trust in leader and the psychological well-being of the workers.